2014
DOI: 10.1128/jvi.02593-13
|View full text |Cite
|
Sign up to set email alerts
|

TRIM13 Is a Negative Regulator of MDA5-Mediated Type I Interferon Production

Abstract: Retinoic acid-inducible gene I (RIG-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 46 publications
1
75
0
1
Order By: Relevance
“…MDA5 was reported to be negatively regulated by another E3 ubiquitin ligase, TRIM13 [83]. This study showed that overexpression of TRIM13 inhibited MDA5-mediated signaling.…”
Section: The Role Of Ubiquitin In Rlr Signal Transductionmentioning
confidence: 96%
See 1 more Smart Citation
“…MDA5 was reported to be negatively regulated by another E3 ubiquitin ligase, TRIM13 [83]. This study showed that overexpression of TRIM13 inhibited MDA5-mediated signaling.…”
Section: The Role Of Ubiquitin In Rlr Signal Transductionmentioning
confidence: 96%
“…This study showed that overexpression of TRIM13 inhibited MDA5-mediated signaling. Furthermore, infection with encephalomyocarditis virus (EMCV) induced significantly higher type-I IFN levels in trim13 −/− mice than in WT mice [83]. In support of this, trim13 −/− mice had an increased resistance to EMCV infection than their WT littermates.…”
Section: The Role Of Ubiquitin In Rlr Signal Transductionmentioning
confidence: 99%
“…1). Interestingly, many ubiquitin related proteins are induced by IFN to enhance (TRIM25) or to block (TRIM13 or 21) the IFN response (Zhang et al, 2013a; Narayan et al, 2014). Similarly, many viruses express ubiquitin ligases or DUBs to alter ubiquitin regulation and favor replication (Kwon and Ahn, 2013) or express proteins that block the action of several ubiquitin enzymes that lead to the activation of the IFN pathway (Rajsbaum et al, 2012).…”
Section: Protein-modulated Control Of the Antiviral Responsementioning
confidence: 99%
“…For example, TRIM5a was documented to have a restrictive ability against HIV-1 and other retroviruses [3,4]. TRIM13 has recently been reported to be a negative regulator of MDA5-mediated type I interferon production [5]. TRIM38 enabled to mediate lysosome-dependent degradation of TAB2/3 to inhibit the NF-κB signaling pathway [6].…”
Section: Introductionmentioning
confidence: 99%